Ability, Examination and Inclusive Education: Stretching the Hard Lines of the Educational System - Halis Sakiz (Educational Process: International Journal)
The aim of this paper is to delve into the debate about the epistemological nature of ability and examination, which we have been continuously exposed to, but rarely scrutinized. In the paper, I refer to Turkey as a case and argue that the dominance of ability-based paradigm and its associated assessment and placement systems have created a new educational order which categorizes schools and students based on how they perform at a single point in time. What is more, I critically evaluate the construction of “abilities” and “disabilities” through the means employed in the education system, followed by a discussion of the examination culture as a product of an ability-based system. Finally, I propose inclusive education as a powerful means of transforming the education system to an equitable and educationally effective one in which all students are welcomed and provided with education of good quality that both enriches childhood and maximizes chances of leading a fulfilled adult life.